Qualidade dos processos mecanizados de semeadura e colheita na cultura da soja - Holanda, Henrique Vinicius de [UNESP] (2015)
Mechanically perform the soybean seeding in the appropriate population distribution of seeds in efficiently seeding line and harvest it mechanically also reducing losses and grains breaks, both are important factors in the mechanized processes of this culture to ensure high productivity. Assuming that the seeding and harvest process of soybean may influence the quality indicators of these mechanized agricultural operations, was conducted this study in the experimental area of the Laboratory of Agricultural Machines and Mechanization of UNESP/Jaboticabal, in order to assess the quality of seeding and harvest of this oilseed through statistical process control. Seeding operation was performed three forward speeds function (4.7, 6.0 and 9.0 km h-1), two populations of plants (400 and 533 thousand plants ha-1), evaluating the strength and power necessary for the process, the longitudinal distribution of plants in the seeding line and agronomic characteristics of the crop. In mechanical harvesting of soybeans using statistical control tools, were evaluated the quantitative losses and operational quality of harvest. Using the criteria of quality control, the sampled area consisted of 30 specialized points, equally spaced at 40 meters, selected sequentially from the beginning of harvest. Each point was determined cutting height; grain moisture at harvest; losses on the platform, internal mechanisms, disability of cutting height and total; percentage of whole and broken grain in bulk, in the platform and track system and cleaning. The results demonstrated that the higher seeding rate resulted in a higher average and peak power demand as well as the lowest percentage of normal spacing between plants. The grain yield was higher in the population initially desired to 533,333 plants ha-1 at the speed of 6 km h-1. The lower operating speed provided less tractor power demand as well the best longitudinal distribution of normal spacing. At harvest ...